2021
DOI: 10.1017/s1049023x21000881
|View full text |Cite
|
Sign up to set email alerts
|

Health Trends among 9/11 Responders from 2011–2021: A Review of World Trade Center Health Program Statistics

Abstract: Introduction: In a single day, the September 11, 2001 US terrorist attacks (9/11) killed nearly 3,000 people, including 412 first responders. More than 91,000 responders were exposed to a range of hazards during the recovery and clean-up operation that followed. Various health programs track the on-going health effects of 9/11, including the World Trade Center (WTC) Health Program (WTCHP). The objective of this research was to review WTCHP statistics reported by the Centers for Disease Control and Prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…A total of 66 studies were identified in our systematic search of the four main databases. During the literature selection process, we excluded studies related to the World Trade Center (WTC) disaster that occurred on September 11, 2001 [ 82 ]. The WTC disaster released a large quantity and variety of toxicants into the environment, affecting rescue and recovery workers as well as community members.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 66 studies were identified in our systematic search of the four main databases. During the literature selection process, we excluded studies related to the World Trade Center (WTC) disaster that occurred on September 11, 2001 [ 82 ]. The WTC disaster released a large quantity and variety of toxicants into the environment, affecting rescue and recovery workers as well as community members.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 9/11 responders using a full diagnostic assessment 11-13 years after the disaster found that 18% had a history of 9/11-related PTSD while 10% of the responders were still present (not remitted). 7 A large cohort of (> 91000) responders to the 9/11 attacks was assessed as part of a worker health care program, and a recent review of this work 8 found that in the second decade after the attacks, 16% still had current MH problems of which 11% were with PTSD, 3% with depression, and 3% with anxiety disorder. These disorders were assessed using a combination of structured diagnostic interviews, self-report symptom checklists, and clinician assessments or mental health treatments at different points in time.…”
Section: Introductionmentioning
confidence: 99%
“…Although the International Agency for Research on Cancer (IARC) has identified outdoor air pollution as carcinogenic to humans, a recent IARC report has classified firefighting as only a possible carcinogen (Group 2B) (IARC 2013 , 2021 ; Barros et al 2021 ). However, some studies (Daniels et al 2014 ; Jalilian et al 2019 ; Soteriades et al 2019 ; Pinkerton et al 2020 ; Laroche and L'Espérance 2021 ; Smith et al 2021 ) indicated a significant increase in the incidence of, among others, rectal, prostate, bladder and testicular cancer, as well as mesothelioma and malignant melanoma in firefighters compared to the general population. Cancer as well as cardiovascular disease (sudden cardiac death (SCD) causes about 45% of on-duty fatalities) are the leading cause of death in this occupational group (International Association Of Fire Fighters—IAFF n.d. ; Soteriades et al 2011 ; Daniels et al 2014 ; Smith et al 2019b ).…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that diseases such as cancer, lung disease, heart disease, and post-traumatic stress disorder appear to be more common in World Trade Center terrorist rescue workers than in the general population, even now over 20 years later (Smith et al 2021 ), and the risk of cancer death (e.g., in lung cancer and leukemia) increases with longer and frequent firefighters’ exposure to the fire environment (Daniels et al 2015 ). The impact of occupational exposure of firefighters on their health has been intensively studied in recent years, but still the evidence suggesting a cause-and-effect relationship is limited and unclear (Barros et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%